Foreign accents reduce false recognition rates in the DRM paradigm. Issue 5 (18th August 2019) - Romero-Rivas, Carlos; Thorley, Craig; Skelton, Katie; Costa, Albert
ABSTRACT: More cognitive resources are required to comprehend foreign-accented than native speech. Focusing these cognitive resources on resolving the acoustic mismatch between the foreign-accented input and listeners' stored representations of spoken words can affect other cognitive processes. Across two studies, we explored whether processing foreign-accented speech reduces the activation of semantic information. This was achieved using the DRM paradigm, in which participants study word lists and typically falsely remember non-studied words (i.e. critical lures) semantically associated with the studied words. In two experiments, participants were presented with word lists spoken both by a native and a foreign-accented speaker. In both experiments we observed lower false recognition rates for the critical lures associated with word lists presented in a foreign accent, compared to native speech. In addition, participants freely recalled more studied words when they had been presented in a native, compared to a foreign, accent, although this difference only emerged in Experiment 2, where the foreign speaker had a very strong accent. These observations suggest that processing foreign-accented speech modulates the activation of semantic information. Highlights The DRM paradigm was used to explore whether semantic activation is reduced when processing foreign-accented speech. Across two experiments, false recognition of non-studied semantic associates was lower when word lists were presented in a foreign accent, compared to native speech. The above results suggest semantic activation may be reduced when processing foreign-accented speech. Additionally, it was found that when the foreign speaker had a mild accent, correct recall of studied words was uninfluenced. If the foreign speaker had a strong accent, however, correct recall of studied words was reduced.